Synthesis of New Diketopiperazines, Thiolation to Thiodiketopiperazines, and Examination of Their ROS‐Generating Properties. Issue 31 (29th September 2015) - Zhong, Sabilla; Wandler, Angela E. E.; Schepers, Ute; Nieger, Martin; Bräse, Stefan
Abstract: A variety of new symmetrical and unsymmetrical diketopiperazines have been prepared from free amino acids by using a previously developed microwave‐assisted protocol. This included the successful incorporation ofL ‐pyroglutamic acid as an unusual building block. The diketopiperazines were then thiolated electrophilically to the corresponding bis(methylthio)‐ and epidithiodiketopiperazines. Initial experiments showed a promising activity towards the generation of reactive oxygen species in HeLa cells. Abstract : A variety of novel symmetrical and unsymmetrical thiodiketopiperazines have been prepared by methyl dichlorophosphite assisted dimerization of free amino acids and by thiolation of the resulting cyclic dipeptides with elemental sulfur and NaHMDS. Some of the sulfur compounds showed interesting activity in the generation of reactive oxygen species in HeLa cells.